Integrative Korean Medicine Treatment for Temporomandibular Disorder and Facial Paresthesia after Tumor Removal Surgery: A Case Report (Case Report Guidelines-Compliant) - Min-Sun Kim; Hungu Lee; Yoojun Yoon; Ji-Su Lee; Yong-Suk Kim; Seunghoon Lee (Journal of Acupuncture Research)
This report presents the case of a 39-year-old male with left temporomandibular joint movement disorder and left facial sensory abnormalities after a trigeminal nerve tumor removal. Integrative Korean medicine treatments, including acupuncture, electroacupuncture, pharmacoacupuncture, Chuna manual therapy, wet-cupping, and herbal medicine administration, were performed on the patient. Post treatments, the patient’s visual analog scale score for pain decreased, the Jaw Functional Limitation Scale-8 scores improved, and significant improvements in chewing and yawning were noted. The patient’s maximum unassisted opening increased to 50 mm, as confirmed using temporomandibular joint radiography. However, further research is required to evaluate the individual effects of the integrative Korean medicine treatments and their overall effectiveness.